Respuesta productiva, pH, morfometría ósea e intestinal y sus relaciones en broilers alimentados con acidificantes protegidos y no protegidos y antibióticos - Céspedes Gaspar, Rubén (2023)
The aim of this study was to evaluate the effect of supplementation with protected (POA) and non-protected organic acids (UOA) on growth performance, pH of the gastrointestinal tract (GIT), bone and intestinal morphometry in diets with antibiotics and their relationships. The study included 200 1-day-old Cobb 500 male broilers. The birds were randomly distributed in 5 treatments with 4 repetitions and 10 birds per replicate. The diets were: T1: control diet; T2: T1 + zinc bacitracin (50 ppm); T3: T2 + unprotected acidifier (500 g/t); T4: T2 + protected acidifier (500 g/t); T5: T2 + protected acidifier (1000 g/t). On day 42 two birds were slaughtered per unit. The data were analysed under a completely randomized design, the comparison of means with the Tukey test and the Pearson correlation test to establish relationships between variables. The results indicated that both POA and UOA did not influence the productive response. The pH of the cecum was higher in T4 over T2. In bone morphometry, T5 presented a better internal diameter than T2 and bone width than T2 and T3. Intestinal morphometry was significant in the jejunum in the crypt height/depth ratio favourable to T3, T4 and T5 over T2 (p<0.05). Negative relationships were found between crop pH and live weight, breast weight, tibia width and crypt height/depth ratio (-0.37, -0.34, -0.36, -0.36 respectively; p<0.05), as well as between the pH of the cecum and the area of the villi of the ileum (-0.41) and the pH of the gizzard and the height of the villi of the ileum (-0.34). It is concluded that no influence was evident in the addition of POA and UOA on the productive parameters, pH of the GIT, bone and intestinal morphometry in broiler chickens fed with antibiotics. Furthermore, moderate negative relationships were found in the pH of the anterior and posterior GIT with production parameters and intestinal morphometry, respectively.